2018
DOI: 10.1016/j.archoralbio.2018.01.017
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro study on the influence of viscosity and frequency of application of fluoride/tin solutions on the progression of erosion of bovine enamel

Abstract: Under the conditions of this short-term in vitro experiment, it could be concluded that increasing the viscosity of the oral rinse solutions reduced enamel loss by erosion; however, this effect was small and only observed when the solutions were applied once a day.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 26 publications
0
16
0
6
Order By: Relevance
“…One important aspect when studying filmforming polymers is the fact that many of them are thickening agents, which means that they could increase the viscosity of solutions [Ávila et al, 2017]. It is known that the viscosity of a solution can affect its anti-erosive potential [Sakae et al, 2018], since we envision their use as additives to mouth rinses, it is necessary to verify how they would affect their final viscosity. Zeta potential is the electrostatic potential of the hydroxyapatite surface that extends to the liquid phase, when the ions on the surface are in equilibrium with those of the solution [Young et al, 1997].…”
Section: Introductionmentioning
confidence: 99%
“…One important aspect when studying filmforming polymers is the fact that many of them are thickening agents, which means that they could increase the viscosity of solutions [Ávila et al, 2017]. It is known that the viscosity of a solution can affect its anti-erosive potential [Sakae et al, 2018], since we envision their use as additives to mouth rinses, it is necessary to verify how they would affect their final viscosity. Zeta potential is the electrostatic potential of the hydroxyapatite surface that extends to the liquid phase, when the ions on the surface are in equilibrium with those of the solution [Young et al, 1997].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that increasing the viscosity of fluoride‐containing solutions (NaF and/or NaF/AmF/SnCl 2 ) improves their enamel erosion reducing effects in a 5‐d erosion experiment involving four daily applications of 0.3% citric acid for 5 min (19) and in a 10‐d experiment involving six daily applications of 0.5% citric acid for 2 min (18). However, there is no study testing the effect of the addition of chitosan to the fluoride solutions with respect to dentin erosion in these experimental circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the increased viscosity in fluoridated (NaF and amine fluoride — AmF) solutions containing stannous ions reduced enamel erosion in a 5 d (19) and 10 d experiment (18). However, there is only one study on the effect of chitosan solution and AmF/NaF/SnCl 2 (not associated with chitosan) on the prevention of dentin erosion (20).…”
mentioning
confidence: 99%
“…These deposits behave as a physical barrier that reduces contact of the acids with the underlying enamel and act as a mineral reservoir which is first attacked by the erosive challenge [Magalhães et al, 2011]. Therefore, to standardize the pH conditions and favor the deposition of these precipitates, the pH of the prepared fluoride solutions was adjusted to 4.5 [Sakae et al, 2018;Bezerra et al, 2019]. Additionally, this acidic pH of the solutions allowed the maintenance of a low viscosity in the solutions associated with Carbopol.…”
Section: Discussionmentioning
confidence: 99%
“…In order to avoid a potential confounding factor [Sakae et al, 2018], the dynamic viscosity of the solutions was determined using a vibroviscosimeter (SV-10, A&D, Toshima-ku, Tokyo, Japan). The results were obtained in duplicate in a temperature-controlled room (25 ° C ± 1 ° C).…”
Section: Preparation Of the Solutions And Measurement Of Their Viscositymentioning
confidence: 99%